2012
DOI: 10.1136/oemed-2011-100463
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lymphocyte subsets in workers exposed to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)

Abstract: Overall, our study showed that plasma TCDD levels had no effect on white blood cell counts and major subsets. However, a non-significant decrease in most lymphocyte subsets was noted, with the strongest effect for B cells. The latter finding may suggest that dioxin exposure might have an adverse impact on the haematopoietic system and lends some support to B cell lymphoma induction by dioxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Participants were asked to complete a self‐administered questionnaire, which included questions on occupational history, personal medical history, medication used in the weeks prior to the blood collection, anthropometric characteristics, smoking status and alcohol intake. Blood plasma samples were collected according to a standard protocol during home visits between May 2007 and September 2008 [Boers et al, ; Saberi Hosnijeh et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to complete a self‐administered questionnaire, which included questions on occupational history, personal medical history, medication used in the weeks prior to the blood collection, anthropometric characteristics, smoking status and alcohol intake. Blood plasma samples were collected according to a standard protocol during home visits between May 2007 and September 2008 [Boers et al, ; Saberi Hosnijeh et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…A possible association between TCDD exposure and NHL risk was recently confirmed in a follow-up of this cohort (Boers et al 2010). It was found that most lymphocyte subsets, in particular the B cell compartment, decreased in absolute counts with increasing TCDD exposure levels (Saberi Hosnijeh, Lenters, et al 2012). Moreover, blood levels of most cytokines, chemokines, and growth factors had a negative association with TCDD levels with a formal statistical significance for fractalkine, transforming growth factor alpha (TGF-), and fibroblast growth factor 2 (FGF2) (Saberi Hosnijeh, ).…”
Section: Tcdd Exposurementioning
confidence: 82%
“…The studied participants were among the highest exposed occupational individuals, based on blood TCDD concentrations, and certainly higher than the levels that have been found in environmental settings Saberi Hosnijeh, Lenters, et al 2012). The main findings of the relevant published studies that investigated immunological changes in relation to dioxin exposure are summarized in Table 1. 5.1.1.…”
Section: Tcdd Exposurementioning
confidence: 99%
See 2 more Smart Citations